Muscle Vanishing in Poliomyelitis Manifested on F-18 FDG PET/CT: An Interesting Imaging Finding - Rong-Hsin Yang; Yum-Kung Chu (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2017)
Muscle atrophy is the loss of muscles bulk; it can be a partial or complete wasting away of muscle. Herein, we describe a 56-year-old man with diffuse large B-cell lymphoma underwent F-18 FDG PET for postchemotherapy evaluation. Fused PET/CT image showed a successful response to treatment and an interesting instance of complete muscle vanishing, attributed to poliomyelitis sequelae. Muscle atrophyseen in polio patients is the result of destruction of motor neurons caused by the poliovirus. CT and MRI are prevalent tools for assessing muscular pathology. As a glucose analog, F-18 FDG PET can provide greater insight into glucose metabolism of the skeletal muscle. F-18 FDG distribution is the crucial information to make it possible for clinicians to fully interpret the functional integrity of the muscles, and to determine if specific procedures are beneficial. Straightforward exhibition of F-18 FDG uptake appears to add validity of donor muscle selection before polio-corrective surgery, and of monitoring after treatment.